The Dividing Line: Academic Forms and Experimentations - Chitrakar, Madan (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
The perception of ‘Art’ has had changed phenomenally since the earliest appearance of art like Painting or Sculpture on the surface of earth. The numerous shifts to new forms and manifestations since then are attributed to the basic human instincts - like desire for continual change and explore for new. But all the changes are always being determined by the motives of the involved artists. Like elsewhere, Nepali Art too has had witnessed multiple forms and phases as time moved on. In the recent times, Art here too, is defined as experimental – an end result of creative experiments. And an argument that today is an age of unlimited freedom - to imagine and to create. But lately, it is found there have been frequent instances of abusing this creative freedom. To correct such tendencies in time, the concerned authorities have designed the related curriculum of Higher Education in Fine Arts – so that the exercise to experiment in ‘Art’ is made only after a designated stage of academic learning – not earlier. Obviously, the point is to lay the due emphasis on learning of academic forms first before exercising creative freedom – called ‘Experimental Art’.